Efficient Generation of Motion Transitions Using Spacetime Constraints - Cohen, Michael; Guenter, Brian; Bodenheimer, Bobby; Rose, Charles (SIGGRAPH 96, 1996)
This paper describes the application of spacetime constraints to creating transitions between segments of human body motion. The motion transition generation uses a combination of spacetime constraints and inverse kinematic constraints to generate seamless and dynamically plausible transitions between motion segments. We use a fast recursive dynamics formulation which makes it possible to use spacetime constraints on systems with many degrees of freedom, such as human figures. The system uses an interpreter of a motion expression language to allow the user to manipulate motion data, break it into pieces, and reassemble it into new, more complex, motions. We have successfully used the system to create basis motions, cyclic data, and seamless motion transitions on a human body model with 44 degrees of freedom.